The social environment of talent development in youth sport - Kristoffer Henriksen; Natalia Stambulova (Frontiers Media S.A., 2023)
During the last decade, talent identification and development research that favours an individual perspective has been complemented by a focus on young athletes' social environments, termed "athletic talent development environments" (ATDEs). Two major lines of research have created a foundation for an ecological vision of talent development as the mutual accommodation between athletes and their ATDEs and of career development as an athlete's journey through various athletic and non-athletic environments. The Talent Development Environment Questionnaire allows the quantitative screening of athletes' environments, while the holistic ecological approach (HEA) promotes in-depth qualitative case studies of ATDEs. In this chapter, we focus mainly on the HEA, including: (a) two models that combine to illustrate an ATDE; (b) a summary of empirical case studies of successful environments in various sports and countries, culminating in a set of shared features of ATDEs that promote athletes' wellbeing and athletic and personal development; (c) an overview of recent trends within HEA (e.g. interorganisational collaboration in talent development) and (d) recommendations for coaches and sport psychology consultants, emphasising the importance of integrating efforts across the whole environment and building strong and coherent organisational cultures. In the discussion, we elaborate on developing the HEA discourse and point to future challenges for researchers and practitioners.